Optimizing the charge profile: Considering users' driving profiles - Fabian Kley; David Dallinger; Martin Wietschel (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2010)
PHEVs are discussed controversially. On the one hand, the evolutionary approach of a hybrid vehicle helps the consumer to adopt to electric driving, using the range extender when driving longer distances. On the other hand, PHEVs have a more complex propulsion system and a potentially low emission impact due to a low electric driving share. These factors, however, strongly depend on the consumers' driving and charging behavior. Therefore, this paper simulates realistic driving based on the national German travel survey. Firstly, battery profiles are modeled using further information about parking locations, charging scenarios, as well as different battery sizes. Secondly, total costs of different alternative vehicles are calculated and minimized varying the battery size. According to the simulation, PHEVs are less expensive and thus important for market adoption. High electric driving shares of more than 80% allow fair emission reductions. And for the few longer trips, PHEVs can use the fall-back option of the internal combustion engine. PHEVs thus do not require an oversized battery and are thus more economical. In the early market, PHEVs will be equipped with smaller batteries; and with higher market share, require customization of the battery size for different customer segments and vehicle types.
urn:nbn:de:0011-n-1450093
Keywords: 330; Batterie; Elektrofahrzeug; Verkehrsverhalten